Generalist-feeding subterranean mites as potential biological control agents of immature corn rootworms - Prischmann, DA; Knutson, E.M.; Dashiell, Kenton E.; Lundgren, Jonathan G. (Springer, 2011)
Predatory mites are important components of subterranean food webs and may help regulate densities of agricultural pests, including western corn rootworms (Chrysomelidae: Diabrotica virgifera virgifera). Implementing conservation and/or classical biocontrol tactics could enhance densities of specialist or generalist predatory mites and lead to pest suppression, but first relevant mite species must be identified and their predatory capabilities evaluated. We conducted lab assays to quantify consumption of immature rootworms and oviposition rates of various mite species. Our study indicates that rootworms are a sub-optimal food source for the mite taxa tested. However, all mite species fed upon rootworms to some degree, although consumption by nematophagous Eviphis ostrinus was extremely low. Predators consumed more rootworm larvae than eggs, and mite size was correlated with prey consumption, with larger predators eating more prey. Four mite taxa (Gaeolaelaps sp., S. miles, Gl. americana, and G. aculeifer) had detrimental effects on survival of rootworm larvae, and the latter two species also had negative impacts on densities of pest eggs. Although it is unlikely that any of these mite species by itself has a major impact on rootworm control, the community of generalist soil-dwelling mites may play an important role in regulating immature rootworm populations in the field.